Analysis of the Cleavage Mechanism by Protein-Only RNase P Using Precursor tRNA Substrates with Modifications at the Cleavage Site. Issue 24 (4th December 2016) - Walczyk, Dennis; Gößringer, Markus; Rossmanith, Walter; Zatsepin, Timofei S.; Oretskaya, Tatiana S.; Hartmann, Roland K.
Abstract: Ribonuclease P (RNase P) is the enzyme that endonucleolytically removes 5′-precursor sequences from tRNA transcripts in all domains of life. RNase P activities are either ribonucleoprotein (RNP) or protein-only RNase P (PRORP) enzymes, raising the question about the mechanistic strategies utilized by these architecturally different enzyme classes to catalyze the same type of reaction. Here, we analyzed the kinetics and cleavage-site selection by PRORP3 from Arabidopsis thaliana ( At PRORP3) using precursor tRNAs (pre-tRNAs) with individual modifications at the canonical cleavage site, with either R p- or S p-phosphorothioate, or 2′-deoxy, 2′-fluoro, 2′-amino, or 2′-O-methyl substitutions. We observed a small but robust rescue effect of S p-phosphorothioate-modified pre-tRNA in the presence of thiophilic Cd 2 + ions, consistent with metal-ion coordination to the (pro-) S p-oxygen during catalysis. S p-phosphorothioate, 2′-deoxy, 2′-amino, and 2′- O -methyl modification redirected the cleavage mainly to the next unmodified phosphodiester in the 5′-direction. Our findings are in line with the 2′-OH substituent at nucleotide − 1 being involved in an H-bonding acceptor function. In contrast to bacterial RNase P, At PRORP3 was found to be able to utilize the canonical and upstream cleavage site with similar efficiency (corresponding to reduced cleavage fidelity), and the two cleavage pathways appear less interdependent than in the bacterial RNA-based system. Graphical Abstract: Highlights: (a) Cleavage mechanism by Arabidopsis thaliana PRORP3; (b) Phosphorothioate and 2′-modifications at cleavage site Evidence for metal-ion coordination to the (pro-) S p-oxygen during catalysis Key role of 2′-OH substituent at nucleotide − 1, likely an H-bond acceptor function Nt − 1/+1 and − 2/− 1 cleavage pathways are less interdependent than for bacterial RNase P.